Letter to Jane Tolmach from Robert D. Willis - Robert D. Willis:::::: (1976)
This letter, dated March 19, 1976, is from Robert D. Willis of Ventura to Jane Tolmach. Willis explains that he serves on the Legislative Committee of the Independent Insurance Agents Association of California and conveys greetings from Ray King. He states that after the primary election, he expects to provide financial support on behalf of the association. In the meantime, he asks her to accept a small personal contribution.